Clinical spectrum and genetic variations of LMNA-related muscular dystrophies in a large cohort of Chinese patients. Issue 5 (22nd June 2020) - Fan, Yanbin; Tan, Dandan; Song, Danyu; Zhang, Xu; Chang, Xingzhi; Wang, Zhaoxia; Zhang, Cheng; Chan, Sophelia Hoi-Shan; Wu, Qixi; Wu, Liwen; Wang, Shuang; Yan, Hui; et al.
Abstract : Background: LMNA -related muscular dystrophy is caused by mutations in LMNA gene. We aimed to identify genetic variations and clinical features in a large cohort of Chinese patients with LMNA mutations in an attempt to establish genotype-phenotype correlation. Methods: The clinical presentations of patients with LMNA -related muscular dystrophy were recorded using retrospective and prospective cohort study. LMNA mutation analysis was performed by Sanger sequencing or next-generation sequencing. Mosaicism was detected by personal genome machine amplicon deep sequencing for mosaicism. Results: Eighty-four patients were identified to harbour LMNA mutations. Forty-one of those were diagnosed with LMNA -related congenital muscular dystrophy (L-CMD), 32 with Emery-Dreifuss muscular dystrophy (EDMD) and 11 with limb-girdle muscular dystrophy type 1B (LGMD1B). We identified 21 novel and 29 known LMNA mutations. Two frequent mutations were identified: c.745C>T and c.1357C>T. A correlation between the location of mutation and the clinical phenotype was observed: mutations affecting the head and coil 2A domains mainly occurred in L-CMD, while the coil 2B and Ig-like domains mainly related to EDMD and LGMD1B. We found somatic mosaicism in one parent of four probands. Muscle biopsies revealed 11 of 20 biopsied L-CMD exhibited inflammatory changes, and muscle cell ultrastructure showed abnormal nuclear morphology. Conclusions: Our detailed clinical and genetic analysis of 84 patients with LMNA -related muscular dystrophy expands clinical spectrum and broadens genetic variations caused by LMNA mutations. We identified 21 novel and 29 known LMNA mutations and found two frequent mutations. A correlation between the location of mutation and the clinical severity was observed. Preliminary data suggested that low-dose corticosteroid treatment may be effective.